Effect of firefighter boots and viscoelastic insoles on the impact force of the ground reaction force’s vertical component - Cámara-Tobalina, Jesús (2011)
The aims of the present study were to determine the effect of firefighter's boots on the vertical component of the ground reaction force (GRF) at heel strike, also known as heel strike transient and to analyze the effect of the viscoelastic insoles placed into the firefighter’s boots on this force during the gait. The magnitude of the impact force (FZI) from the vertical ground reaction force, the time to the production of this force (TZI) and the loading rate (GC) were registered. 39 firefighters without any pathology during 2 years before the study were recruited. Three different walking conditions were tested: 1) gait with firefighter's boots, 2) gait with firefighter's boots and viscoelastic insoles and 3) gait with sport shoes. The results showed a higher production and magnitude of the impact force during gait with firefighter's boots than during gait with sport shoes (13,1 vs. 2,6 % of occurrence of the impact force and 61,39 ± 35,18 %BW (body weight) vs. 49,38 ± 22,99 %BW, respectively). The gait with viscoelastic insoles placed into the firefighter's boots did not show significant differences in any of the parameters characterizing the impact force compared to the gait without insoles. The results of this study show a lower cushioning of the impact force during the gait with firefighter's boots in comparison to the gait with sport shoes and the inefficiency of the viscoelastic insoles placed inside the firefighter's boots to ameliorate the cushioning of the impact force at natural walking speed.